Target blood pressure in patients with chronic kidney disease on maintenance hemodialysis using ambulatory blood pressure monitoring for 72 h – A prospective observational study - Vishal Mangal; Ranjith Nair; Kaminder Bir Kaur; Sachin Maggo (Archives of Medicine and Health Sciences, 2020)
Background and Aim: The target blood pressure (BP) in CKD patients on hemodialysis (HD) remains a dilemma. We aimed to study the BP value most representative of the presence or absence/control of hypertension in CKD patients on HD, and how well could ambulatory BP monitoring (ABPM) predict the presence of hypertension. Materials and Methods: A total of 39 patients with CKD on twice-weekly HD were included in the study. BP was recorded with the help of the sphygmomanometer installed in the HD machine at regular intervals, and the same was compared with ABPM continuously for 72 h during the interdialytic period. Bland–Altman analysis and receiver operating characteristic curve were analyzed. Results: The difference between the mean predialysis systolic blood pressure (SBP) and mean ambulatory SBP was 9.09 mmHg (95% confidence interval [CI], -22.92 to + 41.099 mmHg); however, the difference of 4.86 mmHg (95% CI, -17.886 to + 27.606 mmHg) between the mean diastolic ABPM reading and the mean predialysis diastolic BP did not achieve significance. Conclusion: The data suggest that predialysis office SBP invariably overestimates BP and should not be targeted as a BP goal, as it could lead to intradialytic hypotension. For any given SBP, the postdialysis value is more specific in diagnosing hypertension, thereby reflecting a more significant cardiovascular load. To our knowledge this is the first study to use ABPM continuously during the interdialytic period for 72 h.